UTILIZATION OF cpDNA SEQUENCES TO IDENTIFY 15 MANGO ACCESSIONS - Sukartini Sukartini; Taryono Taryono; Panjisakti Basunanda; Rudi Hari Murti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Information about genetic relationship and genetic diversity are an inevitable need in mango breeding program. Base substitution value, genetic distance and grouping of 15 mango accessions based on accessions in chloroplast DNA (cpDNA) among 15 mango accessions were assessed. The samples were originated from Mango Germplasm, Cukur Gondang Research Station of Indonesian Tropical Fruits Research Institute, Pasuruan, East Java. Sequencing of Chloroplast DNA was used to obtain nucleotide sequence data. Paired specific primer rpl20 F - rps12 R and atp F - rbcL R were used for amplification of non-coding area of mango DNA chloroplast and sequencing processes as well. All data were analyzed using Software MEGA 6. The result showed that total numbers and nucleotide base sequences varied among all accessions. All accessions were grouped in five different clusters that might be used as source of parental breeding.